A Study To Assess The Knowledge On Anaemia Mukt Bharat Strategy Among The Rural Population In Uttar Pradesh - Reshmi Rajan; Joel Kurian Shaji; Lakshay Sharma; Arbina Jan; Nikhil Singh; Sonu Kumar; Aanchal; Talagathoti David Ratna Paul (Revista Electronica de Veterinaria, 2024)
Anemia remains a critical public health challenge in India, affecting diverse populations including women, children, and adolescents. Despite efforts through programs like the National Nutritional Anemia Prophylaxis Program (NNAPP), the National Nutritional Anemia Control Programme (NNACP), and the Intensified National Iron Plus Initiative (INIPI), challenges such as poor coverage, inadequate training, and weak supply chains persist. This study evaluates the understanding and perception of the Anemia Mukt Bharat (AMB) strategy among beneficiaries in rural Greater Noida using a cross-sectional quantitative approach. Data were collected from 60 participants aged 15-45 years through a Demographic Performa and a Self-Structured Knowledge Questionnaire. Results show that 40% of participants had poor knowledge, 46.7% had average knowledge, and 13.3% had good knowledge of the AMB strategy. Significant knowledge gaps were noted, particularly related to occupation and birth order. Findings indicate a need for enhanced educational initiatives and targeted outreach to improve awareness and implementation of the AMB program. Recommendations include developing tailored educational campaigns, integrating AMB education into existing health policies, and further research into socio-cultural factors influencing anemia knowledge. Addressing these gaps is crucial for the program's success and for improving anemia control in rural areas.